2020
DOI: 10.31729/jnma.4967
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile and Endoscopic Findings in Patients with Upper Gastrointestinal Bleed Attending a Tertiary Care Hospital: A Descriptive Cross-sectional Study

Abstract: Introduction: Upper gastrointestinal bleeding is a common acute medical emergency. Endoscopyis the gold standard diagnostic and therapeutic tool in the management of upper gastrointestinalbleed. This study was undertaken to address the clinical profile, endoscopic profile, and outcomes inpatients with upper gastrointestinal bleed. Methods: A descriptive cross-sectional study was conducted in a tertiary care teaching hospital inGandaki Province, Nepal from January 2018 to December 2019 after obtaining eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 13 publications
5
9
0
Order By: Relevance
“…Data from various studies conducted in Nepal showed that the mean age of patients was 49±12.64, 49±12.64, and 51.6 years, respectively, which are in line with our study. 6,9,10 However, a study displayed UGIB in the younger age group with the mean age being 45.32±18.47. 4 Manifestations of UGIB can be either obvious or hidden.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Data from various studies conducted in Nepal showed that the mean age of patients was 49±12.64, 49±12.64, and 51.6 years, respectively, which are in line with our study. 6,9,10 However, a study displayed UGIB in the younger age group with the mean age being 45.32±18.47. 4 Manifestations of UGIB can be either obvious or hidden.…”
Section: Discussionmentioning
confidence: 94%
“… 10 However, other studies found peptic ulcer disease as common findings followed by variceal bleeding among patients with UGIB. 4 , 7 , 9 This may be due to difference in socio-economic and demographic difference between the local population where the study was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…15 We found that there were 4 cases (2%) of stomach cancer in the present study and this finding is similar to the study done by Puttaraju et al 11 Bhattarai et al studied 660 patients with upper GI bleeding and found that peptic ulcer and ruptured esophageal varices were the most common causes. 16 14.8% of the patients died. Repeat bleeding episode, varices, and presence of comorbidities were important risk factors for death.…”
Section: Discussionmentioning
confidence: 96%
“…The symptoms depend on both location and severity but may include bright red blood in vomit, cramps in the abdominal region, and shortness of breath. In the United States, over 100,000 people suffer from upper gastrointestinal bleeding, and men are twice as likely to have upper gastrointestinal bleeding [136]. One study showed the use of ingestible capsules to treat gastrointestinal hemorrhaging through balloon tamponade effect [137].…”
Section: Commercialized Platforms For Video Capsule Endoscopymentioning
confidence: 99%